O direito como experiência: a construção da individualidade do homem frente à sociedade, ao Estado e às instituições - Cavazzola Junior, Cesar Augusto (Universidade do Vale do Rio dos Sinos, 2015)
The purpose of this study is to perform an analysis of the human individuality. This by the fact that more and more a speech around the society, collective rights, in fraternity and solidarity, but little of how man can makes use of their individual rights under the collective. In this dialogue, there will be references to the legacy of modernity and the current debate of postmodernity in addition to the multiplication phenomenon of laws and its social effects and the strengthening of the state.
Keywords: Modernidade; Pós-modernidade; Direito; Estado; Sociedade; Leis; Conhecimento; Engenharia Social; Ética; Modernity; Post-modernity; Right; State; Society; Laws; Knowledge; Social Engineering; Ethics; ACCNPQ::Ciências Sociais Aplicadas::Direito